Brno University of Technology Smartphone PPG Database (BUT PPG): Annotated Dataset for PPG Quality Assessment and Heart Rate Estimation - Nemcova, Andrea; Vargova, Enikö; Smisek, Radovan; Marsanova, Lucie; Smital, Lukas; Vitek, Martin (BioMed research international, 2021)
To the best of our knowledge, there is no annotated database of PPG signals recorded by smartphone publicly available. This article introduces Brno University of Technology Smartphone PPG Database (BUT PPG) which is an original database created by the cardiology team at the Department of Biomedical Engineering, Brno University of Technology, for the purpose of evaluating photoplethysmographic (PPG) signal quality and estimation of heart rate (HR). The data comprises 48 10-second recordings of PPGs and associated electrocardiographic (ECG) signals used for determination of reference HR. The data were collected from 12 subjects (6 female, 6 male) aged between 21 and 61. PPG data were collected by smartphone Xiaomi Mi9 with sampling frequency of 30 Hz. Reference ECG signals were recorded using a mobile ECG recorder (Bittium Faros 360) with a sampling frequency of 1,000 Hz. Each PPG signal includes annotation of quality created manually by biomedical experts and reference HR. PPG signal quality is indicated binary: 1 indicates good quality for HR estimation, 0 indicates signals where HR cannot be detected reliably, and thus, these signals are unsuitable for further analysis. As the only available database containing PPG signals recorded by smartphone, BUT PPG is a unique tool for the development of smart, user-friendly, cheap, on-the-spot, self-home-monitoring of heart rate with the potential of widespread using.
Keywords: Smartphone; elektrokardiografie; algoritmy; Algorithms; Česká republika; Signal Processing, Computer-Assisted; Middle Aged; mužské pohlaví; Reference Standards; referenční standardy; Adult; Czech Republic; Heart Rate; databáze faktografické; Photoplethysmography; srdeční frekvence; Artifacts; Electrocardiography; referenční hodnoty; ženské pohlaví; Humans; Reference Values; artefakty; lidé středního věku; dospělí; fotopletysmografie; Female; počítačové zpracování signálu; Databases, Factual; lidé; Male; chytrý telefon